1978
DOI: 10.1111/j.1365-2842.1978.tb01238.x
|View full text |Cite
|
Sign up to set email alerts
|

A survey of partial denture design in general dental practice

Abstract: The objects of this investigation were to discover the methods by which general dental practitioners communicated partial denture designs to dental laboratories and to ascertain the extent to which certain design criteria were being followed. The results of the survey showed that the responsibility for design appeared to be largely delegated to the technician. In most instances cobalt-chromium dentures were produced which would assist in maintaining oral health; however, this was not the case with acrylic dent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
2
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(59 citation statements)
references
References 12 publications
7
48
2
2
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The provision of removable partial dentures is a basic skill that a dentist relies upon when treating partially dentate patients. 7 The General Dental Council requires all new graduates to be competent at 'designing effective indirect restorations and … partial dentures' .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15] The provision of removable partial dentures is a basic skill that a dentist relies upon when treating partially dentate patients. 7 The General Dental Council requires all new graduates to be competent at 'designing effective indirect restorations and … partial dentures' .…”
Section: Discussionmentioning
confidence: 99%
“…It is clear that from the findings from studies performed by the authors, [1][2][3] and other investigators, [4][5][6][7][8][9][10][11][12][13][14][15] there is a fundamental problem with the design and fabrication process of a variety of prostheses in general dental practice, most notably relating to cobalt-chromium removable partial dentures.…”
Section: N B R I E Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Equally there have been a number of surveys which show that in many cases the technicians are asked to design the RPD by the clinician 3,10 and this appears to have been a long standing problem. 14 Previous studies 15 have been carried out which compared the qualifi ed dental surgeons' ability to design partial dentures and communicate the design to the dental technician. The fi ndings showed that newly qualifi ed dental surgeons were more likely to provide designs which were understood by the technician than those surgeons who had been qualifi ed longer.…”
Section: Introductionmentioning
confidence: 99%